2012
DOI: 10.1678/rheology.40.31
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Aqueous Solution of Hydrophobically Modified Ethoxylated Urethane (HEUR) with Fluorescent Probes at Chain Ends: Thinning Mechanism

Abstract: Nonlinear flow behavior and the corresponding fluorescent behavior were examined for a 3.0 wt% aqueous solution of hydrophobically modified ethoxylated urethane (HEUR; M w = 1.1×10 5 ) having fluorescent pyrenyl (Py) groups at the chain ends. These end groups associated with each other to serve as cores of HEUR flower micelles, and these micelles were further connected into super-bridges to form a transient network. Correspondingly, single-Maxwellian relaxation reflecting the thermal reorganization of this net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…where w is the radius of the bleached area (w = 50 μm). the fluorescent-modification was also reported by Suzuki et al 27) Thus, we cannot compare the absolute values with the conventional data, but we believe that the comparison of the FRAP and viscoelastic data using the same sample is permittable.…”
Section: Concentration Dependence Of Linear Viscoelastic Properties Fmentioning
confidence: 86%
See 1 more Smart Citation
“…where w is the radius of the bleached area (w = 50 μm). the fluorescent-modification was also reported by Suzuki et al 27) Thus, we cannot compare the absolute values with the conventional data, but we believe that the comparison of the FRAP and viscoelastic data using the same sample is permittable.…”
Section: Concentration Dependence Of Linear Viscoelastic Properties Fmentioning
confidence: 86%
“…It is seen that β value decreases from around 0.6 to 0.4 with increasing C HEUR , which is also observed in the previous study by Rao et al 25) This result suggests that the heterogeneity increases with C HEUR . It is known that the first-and second-order average relaxation times, <τ KWW > [1] and <τ KWW > [2] , of the KWW function can be determined by the following equations 27) .…”
Section: Characterization Of F-heurmentioning
confidence: 99%
“…The focus on the process of association/dissociation of a polymer chain in solution of this model is well adapted to explain the single-Maxwellian relaxation. Overall, the nonlinear shear thinning behavior of HEUR solutions is explained by the shear-induced fragmentation of the transient network, conversion of superbridges to superloops, leading to the drop of the solution viscosity. However, the shear thickening behavior is not explained by the Tanaka–Edwards model.…”
Section: Structure/rheological Properties Relationshipmentioning
confidence: 99%
“…33,34,35,36,37 On the other hand, Watanabe and co-workers related the thickening to a new approach considering the anisotropy of the transient network. 32,38 Indeed, their model showed that the thickening could arise from the shear enhanced re-association of HEUR strands in the shear gradient direction. This effect was balanced with the dissociation of the network and probably combined to FENE effect and shear induced strand formation.…”
Section: Figure 3: Synthesis Pathways To Uni-heur and S-g Heur With ⃝mentioning
confidence: 99%
“…Following their work, various models have considered the interplay between polymer-and crosslink dynamics as stickers, including the sticky Rouse model 20,21) , sticky reptation model [21][22][23][24] , and reversible gelation model 25,26) . Alternatively, considerable experimental studies have been conducted to elucidate the viscoelasticity of the transient networks by using thermoresponsive ABA block copolymers [27][28][29][30] , hydrophobically end-capped polymers [31][32][33][34][35][36][37] , ionomers 25,[31][32][33][34][35][36][37][38][39][40] , "slime" [41][42][43] , etc. In addition, some studies reported the use of wormlike (threadlike) micelles, which are also strongly relevant [44][45][46][47][48] .…”
Section: Introductionmentioning
confidence: 99%